NF-κB and AP-1 are required for the lipopolysaccharide-induced expression of MCP-1, CXCL1, and Cx43 in cultured rat dorsal spinal cord astrocytes - Lu, Ying; Li, Bo; Xu, Axiang; Liang, Xuan; Xu, Tao; Jin, Huan; Xie, Ye; Wang, Rong; Liu, Xiaohong; Gao, Xiaohong; Han, Yong; Zeng, Junwei (Frontiers in Molecular Neuroscience, 2022)
TLR4 and Cx43 signaling in dorsal spinal cord has been shown to be involved in the development of neuropathic pain. However, it is not clear whether TLR4 signaling is associated with the expression of MCP-1, CXCL1 and Cx43 in LPS (lipopolysaccharide)-treated rat dorsal spinal cord astrocytes under in vitro condition. In the present study, we found that TLR4 antagonist TAK-242 significantly inhibited LPS-induced MCP-1, CXCL1 and Cx43 expression, suggesting the role of TLR4 in response to LPS in cultured dorsal spinal cord astrocytes. Application of TAK-242 significantly blocked LPS-induced NF-κB and AP-1 activity and the expression of MCP-1, CXCL1 and Cx43. Furthermore, NF-κB inhibitor PDTC and AP-1 inhibitor SR11302 significantly blocked LPS-induced MCP-1, CXCL1 and Cx43 expression. DNA-binding activity of NF-κB, its effect on MCP-1 expression was suppressed by PDTC and SR11302. On the other hand, DNA-binding activity of AP-1, its effect on CXCL1 or Cx43 expression was also suppressed by PDTC and SR11302. In addition, PDTC was found to inhibit the nuclear translocation of AP-1 and the expression of c-Jun induced by LPS, which suggested that NF-κBp65 is essential for the AP-1 activity. Similarly, SR11302 significantly blocked LPS-induced the nuclear translocation of NF-κBp65 and the expression of NF-κBp65 induced by LPS. Pretreatment with CBX, Gap26 or Gap19（Cx43 blockers）significantly inhibited abnormal astrocytic hemichannel opening and chemokines (MCP-1 and CXCL1) release in LPS-stimulated astrocytes. In summary, cell culture experiments revealed that LPS stimulation could evoke TLR4 signaling with the subsequent activation of NF-κB and AP-1, resulting in the expression of MCP-1, CXCL1 and Cx43. TLR4 activation increased Cx43 hemichannel, but not gap-junction activities and induced the release of the MCP-1 and CXCL1 from astrocytes via Cx43 hemichannel. These findings may help us to understand the role of astrocytic signaling in inflammatory response within dorsal spinal cord tissue.